Digital Gold- The Current Investment Trend in India - YaminiBhargavi, K.; NeehalikaBavya, S. P. (International Journal of Psychosocial Rehabilitation, 2021)
India has one of the largest millennial populations in the world, making up around 34% of the total population and accounting for a major part of the workforce. Due to increased utilization of technology and recent changes in the business markets, investors have looked up to new investment trends such as “Digital Gold Investments.”. Millennials are early adopters of evolving technologies, as they’re the first generation to be known as digital natives. They tend to use technology, being an integral part of almost everything they do, such as shopping, communicating, listening to music, and investing too. In recent times, by using many personal finance and investment apps that are available in the market today, they have become attracted towards digital investments. Digital gold” provides the investor a chance of owning physical gold with the benefits of new-age technology that eliminates the hassles of inspecting physical gold for purity and then figuring out a secure storage option. Providing them with technology that makes investing in gold digitally accessible and convenient to suit their preference of holding an asset digitally over physically is a smart move. This study has been made to explore the trends in “Gold Investments in India on Digital Platform,” its scope in today’s business markets, applications, effects on investors, and opportunities offered in the present, and its evolution in future periods.